Using Arabic Picture Story Media Enhance Religius Character Student in Primary School - Fajriyah, Ayu Rohmatul; Fahyuni, Eni Fariyatul (Universitas Muhammadiyah Ponorogo, 2024)
This research includes the type of research development that aims to produce products using the Dick and Carey model. The product of Arabic pictorial story media enhance religious students at SD Muhammadiyah I, Lab school Umsida. Data analysis in the form of qualitative and quantitative descriptive questionnaires from technology experts and subject matter experts, as well as comments from students for revision. The arabic pictorial story media enhance religious students were carried out in the form of pre-test and post-test on 32 students with several moral subjects. The pre-test post-test results showed the Sig (2- tailed) value was 0,000 < 0.05, which means that there were differences in learning outcomes between before and then using Arabic pictorial story media. The results of Arabic pictorial story media enhance religious students effective improving has a support level of 89.94% for increasing the involvement religious characters in school.